Innovation in devices for Newborn Stability During transport : A Systematic Literature Review - Widyawati, Melyana Nurul (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2025)
Goal: The development of devices for newborn stability during transport has gained attention, particularly in neonatal care. These devices, with real-time monitoring, aim to reduce risks like hypothermia, respiratory distress, and cardiovascular instability. This systematic literature review examines the current innovations in newborn stabilization devices, exploring their design, functionalities, and the integration of monitoring systems to enhance neonatal outcomes. The review provides an overview of device advancements, assesses their effectiveness in maintaining newborn stability, and discusses the benefits, limitations, and future challenges in their broader application. These innovations hold the potential to revolutionize neonatal transport care, improving safety and survival rates for high-risk infants globally.